" employees voices behaviors: Theoretical concepts and thinking approaches - حمود, سعد علي; صبر, رنا ناصر (Journal of Economics and Administrative Sciences, 2017)
The concept of employees voice has received a great deal of attention by researchers in the field of organizational behavior and human resources management especially in the last three decades of the twentieth century , this importance has deep ranges limits in terms of its discussion history, so it became a behavioral variable received a great attention and care in managerial and organizational studied and basic pillar in the success and excellence of organizations in maintaining its human resources, the research explain the concept and benefits of paying attention to the voice of employees in business organizations , and the theories interpreted to employees voicing and clearing the motivations behind employees voicing, and discussing the behaviors related with employees voicing and explaining the structural models interpreting employees voicing. The research conclude a number of conclusions and recommendations some of them are motivating our organizations and top managements to realize the importance of looking to employees voicing as a business strategy  and not just initiatives to solve temporary issues , and this require merge it in the vision , mission and strategy of the whole organization and consider it a basic part of its culture.